Comparison of opinions of pupils in mining and agricultural communities toward home and social problems - Foss, Rhoda, author; Morgan, David H., advisor; Williamson, Maude, committee member; Eddy, Gladys S., committee member; Fee, Lucile, committee member; Betts, Gilbert L., committee member; Kezer, Alvin, 1877-, committee member; Avery, George T., committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Conduct of life; Social ethics; High school students -- Attitudes